Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar Matematika Siswa Kelas IV di SD Negeri 2 Kalikebo - Nur Sheilla Amin; Tukiyo Tukiyo; Putri Zudhah Ferryka (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This study was conducted to determine the effect of the Problem Based Learning learning model on the mathematics learning outcomes of fourth-grade students of SD Negeri 2 Kalikebo on the material of the area of ​​square and rectangular flat shapes. This study used a quantitative type of quasi-experimental design. The population in this study were all students of SD Negeri 2 Kalikebo and SD Negeri 1 Kalikebo. The sample in this study was fourth-grade students of SD Negeri 2 Kalikebo and SD 1 Negeri Kalikebo. The research instrument was first tested for validity and homogeneity. The results of this study indicate an effect of the Problem Based Learning learning model on the mathematics learning outcomes of fourth-grade students at SD Negeri 2 Kalikebo. Proven by the paired sample t-test hypothesis test obtained a t-count value of 7.311> t-table 2.010 (t-count is greater than t-table) meaning that H0 is rejected and Ha is accepted, it can be concluded that the use of the problem based learning model has an effect on the learning outcomes of fourth-grade students of SD Negeri 2 Kalikebo.